Open-source discovery of chemical leads for next-generation chemoprotective antimalarials. - Antonova-Koch, Y; Meister, S; Abraham, M; Luth, MR; Ottilie, S; Lukens, AK; Sakata-Kato, T; Vanaerschot, M; Owen, E; Rodriguez, JC; Maher, SP; Calla, J; et al. (American Association for the Advancement of Science, 2018)
To discover leads for next-generation chemoprotective antimalarial drugs, we tested more than 500,000 compounds for their ability to inhibit liver-stage development of luciferase-expressing Plasmodium spp. parasites (681 compounds showed a half-maximal inhibitory concentration of less than 1 micromolar). Cluster analysis identified potent and previously unreported scaffold families as well as other series previously associated with chemoprophylaxis. Further testing through multiple phenotypic assays that predict stage-specific and multispecies antimalarial activity distinguished compound classes that are likely to provide symptomatic relief by reducing asexual blood-stage parasitemia from those which are likely to only prevent malaria. Target identification by using functional assays, in vitro evolution, or metabolic profiling revealed 58 mitochondrial inhibitors but also many chemotypes possibly with previously unidentified mechanisms of action.